The enigmatic diploid Chenopodium ucrainicum (Chenopodiaceae / Amaranthaceae s. l.): geographical, ecological, and phytosociological patterns as clues to its origin - Shynder O.I.; Pashkevych N.A.; Kharytonova I.P.; Holovko O.V.; Mandák B.; Mosyakin S.L. (Ukrainian Botanical Journal)
Chenopodium ucrainicum Mosyakin & Mandák (Chenopodiaceae / Amaranthaceae s. l.), a newly described diploid species currently known only from Ukraine, is a distinctive yet still enigmatic element of the Ukrainian flora. This study provides a detailed account of its presently known geographical distribution, ecological preferences, and phytosociological features, plus some further information of its morphology, based on field surveys conducted during 2021–2024 across central and western regions of Ukraine. Our fieldwork targeted synanthropic habitats, including roadsides, ruderal zones, forest edges, and undercanopy areas within anthropogenic forests and urban parks. The known range of C. ucrainicum is fragmented, with major population clusters in the Dnipro Upland, Male Polissia, and the Podillian Upland. The distribution pattern indicates its primary occurrence in synanthropic environments with moderate moisture levels, and its presence in disturbed habitats suggests its likely status as an alien species in Ukraine. Observations also noted its high projective coverage in plant communities associated with Acer negundo and Robinia pseudoacacia, where C. ucrainicum, if present, frequently plays a dominant role among species of the herbaceous layer. A new association, Chenopodio ucrainicae-Aceretum negundi ass. nov., is proposed, highlighting the diagnostic value of C. ucrainicum in ruderal and other anthropogenic plant communities. Ecologically, C. ucrainicum is classified as a mesophyte with a long vegetation period, making it well-suited to warmer climates with extended growing seasons. Its phenological pattern and tolerance to low temperatures point to its supposed origin in and spread from regions with similar climatic conditions. Although the species exhibits high adaptability within its current range, which corresponds to the recent warming climatic trends in Ukraine, its absence in historical records in herbaria supports the hypothesis that C. ucrainicum is a relatively recent immigrant in Ukraine. Its native range may lie in temperate or subtropical regions of southern or southeastern Asia, where other genetically diverse Chenopodium species are present. Continued research, including molecular phylogenetic and phylogeographic studies, will be essential for confirming its actual geographic origin and the evolutionary role within the Chenopodium album allopolyploid complex. This study contributes valuable insights into the distribution patterns and ecological characteristics of C. ucrainicum, highlighting its probable status as an expanding neophyte in the flora of Ukraine, influenced by climate change and anthropogenic factors.